2020
DOI: 10.3390/v12060595
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 14p1 Immunopathogenesis during Lung Infection in the Syrian Hamster

Abstract: Adenovirus (Ad) infections are usually mild and self-limited, with minimal inflammatory responses. During worldwide outbreaks, Ad14p1, an emerging Ad14 variant, has caused severe pulmonary disease, including acute respiratory distress syndrome (ARDS). This increased pathogenicity of Ad14p1 is not completely understood. In initial studies, we observed that infection of Syrian hamsters with Ad14p1 can cause a patchy bronchopneumonia, with an increased intensity of inflammation, compared to wild type Ad14 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Human adenoviruses exhibit species-restricted phenotypes, making studying disease progression in animal models particularly problematic. However, studies of HAdV-B14p1 in the Syrian hamster model have shed some light on virus-mediated immune- and histopathologies [ 19 ]. HAdV-B14p1 is a species B adenovirus (similar to HAdV-B3 and HAdV-B7) implicated in severe pneumonia and ARDS in humans [ 14 ].…”
Section: Cytokine Responses To Adenovirus In Different Biological Con...mentioning
confidence: 99%
See 2 more Smart Citations
“…Human adenoviruses exhibit species-restricted phenotypes, making studying disease progression in animal models particularly problematic. However, studies of HAdV-B14p1 in the Syrian hamster model have shed some light on virus-mediated immune- and histopathologies [ 19 ]. HAdV-B14p1 is a species B adenovirus (similar to HAdV-B3 and HAdV-B7) implicated in severe pneumonia and ARDS in humans [ 14 ].…”
Section: Cytokine Responses To Adenovirus In Different Biological Con...mentioning
confidence: 99%
“…HAdV-B14p1 is a species B adenovirus (similar to HAdV-B3 and HAdV-B7) implicated in severe pneumonia and ARDS in humans [ 14 ]. The infection of Syrian hamsters with HAdV-B14p1 led to a more severe ARDS-like lung pathology compared to infection with the parental HAdV-B14 virus [ 19 ]. In addition to more extensive lung tissue damage, lung immune-pathology in this model included the high expression of pro-inflammatory cytokines IL-1β and TNF-α and chemokines CCL3 and CXCL10 [ 19 ].…”
Section: Cytokine Responses To Adenovirus In Different Biological Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, Radke and colleagues reported that HAdV-B14 and an emerging variant, B14p1, cause severe lung pathogenesis in intratracheally infected in Syrian hamsters characterized by local infiltrations of inflammatory cells developing into bronchopneumonia. However, although the authors did not report clinically apparent disease signs, these studies in conjunction with the studies that Tollefson and colleagues performed in Syrian hamsters allowed for comparisons of the pathogenicity of the different HAdVs and assessment of respective immune responses [ 55 , 56 , 60 , 61 ].…”
Section: Main Textmentioning
confidence: 99%
“…Certain genotypes of a closely related type, HAdV-B14, cause more severe infections than other genotypes within the same serotype. Here, we learn about distinct inflammatory events caused by different genotypes in the Syrian hamster model [3], which have the potential to be useful for dissection of adenovirus genes associated with mild or severe illness. Adenovirus-induced glycolysis is known to be regulated by the protein encoded by the E4orf1 gene.…”
mentioning
confidence: 99%